2003
DOI: 10.1089/109629603766956951
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the TNF-αand TNF-βPolymorphisms upon Infectious Risk and Outcome in Surgical Intensive Care Patients

Abstract: The presence of the A allele at these polymorphic sites did not predispose critically ill surgical patients to either infection or septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Figure 3 illustrates that there was no association between TNF2 and sepsis-related mortality with an odds ratio of 1.48 (95% confidence interval, 0.81-2.70; p ϭ .20). (27) Ϫ ϩ Ϫ ϩ Jessen et al (25) ϩ ϩ ϩ ϩ Sipahi et al (33) Ϫ ϩ Ϫ ϩ Garnacho et al (22) ϩ ϩ Ϫ ϩ Watanabe et al (37) ϩ ϩ Ϫ ϩ Nakada et al (29) Ϫ ϩ Ϫ ϩ Jaber et al (24) Ϫ ϩ ϩ ϩ Gordon et al (23) ϩ ϩ ϩ ϩ Barber et al (18) Ϫ ϩ Ϫ ϩ Zhang et al (39) Ϫ ϩ Ϫ ϩ Zhang et al (40) Ϫ ϩ Ϫ ϩ Treszl et al (36) Ϫ ϩ Ϫ Ϫ Schaaf et al (32) ϩ ϩ Ϫ ϩ Gallagher et al (21) ϩ Ϫ Ϫ ϩ Calvano et al (19) Ϫ ϩ ϩ ϩ O'Keefe et al (31) Ϫ ϩ Ϫ ϩ Majetschak et al (26) Ϫ ϩ Ϫ ϩ Waterer et al (38) Ϫ ϩ ϩ ϩ Appolini et al (17) Ϫ ϩ Ϫ Ϫ Tang et al (35) Ϫ ϩ Ϫ ϩ Nuntayanuwat et al (30) Ϫ ϩ Ϫ Ϫ Mira et al (28) Ϫ ϩ ϩ ϩ Dumon et al (20) Ϫ ϩ Ϫ ϩ Stuber et al (34) Ϫ Stratification by ethnicity indicated that the association between TNF2 polymorphism and susceptibility to sepsis may be more pronounced in Asians as compared with whites (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 illustrates that there was no association between TNF2 and sepsis-related mortality with an odds ratio of 1.48 (95% confidence interval, 0.81-2.70; p ϭ .20). (27) Ϫ ϩ Ϫ ϩ Jessen et al (25) ϩ ϩ ϩ ϩ Sipahi et al (33) Ϫ ϩ Ϫ ϩ Garnacho et al (22) ϩ ϩ Ϫ ϩ Watanabe et al (37) ϩ ϩ Ϫ ϩ Nakada et al (29) Ϫ ϩ Ϫ ϩ Jaber et al (24) Ϫ ϩ ϩ ϩ Gordon et al (23) ϩ ϩ ϩ ϩ Barber et al (18) Ϫ ϩ Ϫ ϩ Zhang et al (39) Ϫ ϩ Ϫ ϩ Zhang et al (40) Ϫ ϩ Ϫ ϩ Treszl et al (36) Ϫ ϩ Ϫ Ϫ Schaaf et al (32) ϩ ϩ Ϫ ϩ Gallagher et al (21) ϩ Ϫ Ϫ ϩ Calvano et al (19) Ϫ ϩ ϩ ϩ O'Keefe et al (31) Ϫ ϩ Ϫ ϩ Majetschak et al (26) Ϫ ϩ Ϫ ϩ Waterer et al (38) Ϫ ϩ ϩ ϩ Appolini et al (17) Ϫ ϩ Ϫ Ϫ Tang et al (35) Ϫ ϩ Ϫ ϩ Nuntayanuwat et al (30) Ϫ ϩ Ϫ Ϫ Mira et al (28) Ϫ ϩ ϩ ϩ Dumon et al (20) Ϫ ϩ Ϫ ϩ Stuber et al (34) Ϫ Stratification by ethnicity indicated that the association between TNF2 polymorphism and susceptibility to sepsis may be more pronounced in Asians as compared with whites (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies (46.8% enrolling 12 409 patients) were conducted solely or partly in the United States,18,20,22,28,3640,42,45,47,50,52,53,55,56,58,6063,67–70,72,75,77,81,82,87,9092,94,95 34 studies (43.0% enrolling 10 096 patients) were conducted exclusively or partly in Europe,16,19,2327,2935,43,44,46,48,49,54,57,59,65,66,73,74,78,80,8386,89,93 and the remainder were conducted in Asia, South America or Australia 17,41,51,64,71,76,79,88. Forty-eight studies (60.8%) recruited subjects from single centers,17,18,22,24,26,27,29,31,3342,44,47,50,52,53,5558,60,61, 63,64,70,71,73,7577,8089,92 16 (20.2%) were multicenter,16,20,21,…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the broad clinical spectrum encompassed by a diagnosis of sepsis, to timing of therapy or patient-specific differences in the innate immune responses to infection [3]. Several genetic factors affect the course of sepsis [108,109], and single nucleotide polymorphisms can greatly affect the serum levels of cytokines such as TNF-α in individuals [110,111]. It is hardly surprising, therefore, that clinical outcomes following hemoadsorption therapy may vary greatly between patients.…”
Section: The Future Of Cytokine Adsorption Therapymentioning
confidence: 99%